2022
DOI: 10.1186/s13033-022-00514-1
|View full text |Cite
|
Sign up to set email alerts
|

Staffing and patient-related factors affecting inpatient falls in a psychiatric hospital: a 5-year retrospective matched case–control study

Abstract: Background The frequency and severity of falls of psychiatric inpatients in Thailand have not been previously reported. Also, the risk factors of falls have been numerous and complicated. This study aimed to investigate the staffing factors and patient-related factors that increase the likelihood of falls among psychiatric inpatients. Methods A five-year retrospective matched case–control study was conducted that selected cases of inpatients who fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…In our study, accidental falls were also reported in a number of facilities. A study done in Thailand reported that falls incidents were more frequent at night and within the first week of admission and that common activities during falls were bathroom-related and getting up from the bed or chair [ 31 ]. A retrospective review of Charts in Belgium reported 4.4 falls per 1,000 patient days, and these falls were linked to mental status of the patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, accidental falls were also reported in a number of facilities. A study done in Thailand reported that falls incidents were more frequent at night and within the first week of admission and that common activities during falls were bathroom-related and getting up from the bed or chair [ 31 ]. A retrospective review of Charts in Belgium reported 4.4 falls per 1,000 patient days, and these falls were linked to mental status of the patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“… 29 The contribution of physical risk factors, such as physical impairments and side effects of medication to falls, is significant in both seclusion and in general psychiatric inpatient care. 30 Therefore, more focus is needed on the physical risk assessment for secluded patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because in seclusion the focus is more on the behavioral disturbance of the patient28 and less on their physical condition 29. The contribution of physical risk factors, such as physical impairments and side effects of medication to falls, is significant in both seclusion and in general psychiatric inpatient care 30. Therefore, more focus is needed on the physical risk assessment for secluded patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, accidental falls were also reported in a number of facilities. A study done in Thailand reported that falls incidents were more frequent at night(and within the rst week of admission and thatcommon activities during falls were bathroom-related and getting up from the bed or chair (23).…”
Section: Types and Frequencies Of Incidentsmentioning
confidence: 99%